A method for testing shear strength of annular coating components
By performing mold design, film curing and universal testing machine loading test on the annular coating sample, combined with the crack surface calibration of the three-dimensional scanner, the accuracy of the shear strength test of the annular coating components is solved, and efficient shear strength evaluation of the large-thick annular coating components is achieved.
Patent Information
- Application Number
- CN202510047408.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-04
AI Technical Summary
The prior art is difficult to accurately test the shear strength of large-thick annular coating members, and calibration errors and test failures are prone to problems.
By dissecting the annular coating sample in half, designing a curing mold and a curing tool, coating the adhesive film and curing it, then loading tests are performed on a universal testing machine, and the fracture surface is calibrated by a three-dimensional scanner to calculate the shear strength.
Accurate shear strength testing of large-thick annular coating components is achieved, reducing test errors and ensuring the accuracy and effectiveness of test data.
Smart Images

Figure CN119757190A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of strength testing, and in particular to a shear strength testing method for an annular coating component. Background Art
[0002] Coating shear strength refers to the ability of a coating to resist relative sliding or shear deformation when subjected to shear force, that is, a performance indicator that measures how much force a coating can withstand in a direction parallel to the interface between the coating and the substrate or between the layers within the coating without being damaged. Coating shear strength is an important parameter for evaluating coating structure and material properties, which directly affects the durability of the coating in actual service conditions.
[0003] At present, the shear strength of the surface coating of flat specimens is mainly tested by the standard of HB 5474-1991 "Test Method for Shear Strength of Thermal Spray Coatings", which is mainly tested by coating and modeling on the surface of flat specimens and stretching. The coating thickness of the test object is less than 1mm. An annular coating component is a component with an annular geometric shape and a coating on the surface, including an annular pipe, annular gasket, etc. The coating is applied to the inner and outer surfaces of the annular component by spraying, electroplating and other processes, thereby improving the wear resistance, corrosion resistance, high temperature resistance and other properties of the component; the coating thickness of the annular coating component is usually greater than 1mm and includes the coating on the inner and outer surfaces, wherein the inner and outer surfaces of the annular coating component are curved surfaces, and its fracture surface is not exactly the same as the adhesive surface of the flat specimen surface, resulting in difficulty in calibrating the fracture area, and prone to omission, mis-marking, wrong marking, etc., or even failure to calibrate. Not only is it easy to have calibration errors and affect the accuracy of the shear strength test, but it is also easy to have problems such as failure to test or test failure, affecting the shear strength assessment of the annular coating component. Summary of the invention
[0004] In view of the problems existing in the above-mentioned prior art, the purpose of the present invention is to provide a shear strength testing method for annular coating components. The testing method is targeted at annular coating components and can accurately and efficiently characterize and evaluate the shear strength of the coating, thereby realizing the shear performance measurement of large-thickness annular coating components.
[0005] The purpose of the present invention is achieved through the following technical solutions: A method for testing the shear strength of an annular coating component, comprising: Step A, mold design: cut the annular coating sample in half, and design a curing mold and a curing tooling according to the cut sample to be tested (the appearance and size of the curing mold should correspond to the sample to be tested); Step B, coating the adhesive film: uniformly coating the adhesive film on the inner and outer surfaces of the sample to be tested, and fixing the sample to be tested coated with the adhesive film by a curing mold and a curing tool; Step C, bonding and curing: placing the curing tooling in step B into an electric hot air drying oven for heating and curing; after curing, the sample to be tested is cooled to room temperature, the curing mold is taken out, and the residual adhesive around the sample to be tested is removed; Step D, loading test: placing the sample to be tested and the curing mold on a universal testing machine through a clamping tool so that the sample to be tested is subjected to a vertical force; starting the universal testing machine to perform a loading test on the sample to be tested; Step E, calibrating the fracture surface: after the loading test is completed, the sample to be tested is taken out, and the surface of the sample to be tested is scanned by a three-dimensional scanner to construct a continuous cross-section model, and the fracture area of the sample to be tested is obtained; Step F, data processing: obtaining the shear strength through the failure load and fracture area of the loading test.
[0006] Based on further optimization of the above scheme, the curing mold in step A includes an outer mold and an inner mold, the outer mold is composed of a coaxial cylindrical portion and a semi-annular portion, the semi-annular portion is arranged corresponding to the sample to be tested and the inner wall of the semi-annular portion can fit with the outer wall of the sample to be tested, the two side planes of the semi-annular portion are flush with the two cross-sections of the sample to be tested, and the inner diameter and outer diameter of the cylindrical portion are consistent with the semi-annular portion; the inner mold is arranged as a rod-shaped structure corresponding to the inner circle of the sample to be tested.
[0007] Based on further optimization of the above scheme, the adhesive film in step B adopts any one of E-7 two-component epoxy adhesive or Fm-1000 solid adhesive film.
[0008] Based on the further optimization of the above scheme, the curing tooling in step B includes an upper tooling and a lower tooling, the lower tooling is provided with a first slot corresponding to the outer wall of the outer mold, and the upper tooling is provided with a second slot corresponding to the semi-circular plane, the cross section of the sample to be tested and the outer wall of the inner mold; the specific installation method is: first, the outer mold is clamped in the first slot; then, the sample to be tested with the inner and outer surfaces coated with adhesive film is placed on the inner wall of the semi-circular part, ensuring that the inner wall of the semi-circular part fits with the outer wall of the sample to be tested and the cross section of the sample to be tested is flush with the plane of the semi-circular part; then, the inner mold is passed through the inner circle of the sample to be tested and the outer wall of the inner mold is tightly fitted with the inner circle of the sample to be tested; finally, the upper tooling is clamped on the outer wall of the inner mold, so that the outer wall of the second slot is respectively fitted with the semi-circular plane, the cross section of the sample to be tested, and the outer wall of the inner mold, and the upper tooling and the lower tooling are fixed by limit bolts to ensure close contact between the coating, the adhesive film and the inner and outer molds.
[0009] Based on further optimization of the above scheme, in step C, the curing temperature is 150-250° C., and the insulation time is 120-180 min.
[0010] Based on further optimization of the above scheme, the clamping tool includes a support plate, a support seat, a positioning nest, a pressure plate and a pressure rod assembly. The support seat is fixedly arranged on the end face of the support plate and the positioning nest is detachably arranged on the end face of the support seat. The outer wall of the support seat corresponds to the inner wall of the outer mold and a through hole is arranged in the middle of the positioning nest corresponding to the inner mold; the pressure rod assembly is detachably arranged on the bottom surface of the pressure plate, including a connecting seat and multiple pressure rods. The connecting seat and the bottom plate of the pressure plate are detachably connected, and multiple pressure rods are evenly arranged on the bottom surface of the connecting seat and corresponding to the sample to be tested.
[0011] Based on the further optimization of the above scheme, the specific method of performing the loading test on the sample to be tested in step D is: First, the support plate is placed on the end surface of the support table of the universal testing machine and a positioning nest is set on the support seat, and the curing mold with the sample to be tested in step C is placed on the end surface of the support plate, wherein the bottom inner wall of the outer mold contacts the outer wall of the support seat (to achieve the positioning of the curing mold and the sample to be tested) and the top of the positioning nest contacts the bottom surface of the sample to be tested, thereby positioning the curing mold and completing the support of the sample to be tested; at the same time, the pressure plate without the pressure rod assembly is installed on the loading end of the universal testing machine; Then, start the universal testing machine, move the pressure plate downward, load the inner mold until the inner mold falls off the inner wall of the test sample, and record the corresponding failure load. F xi ; Finally, the universal testing machine is reset, the outer mold with the sample to be tested is removed, the positioning nest on the support seat is removed, and the pressure rod assembly is installed on the bottom of the pressure plate. The outer mold with the sample to be tested is placed on the support plate again (the support seat is used for limiting so that the outer mold and the pressure rod assembly are coaxial), and the universal testing machine is started, so that the pressure plate drives the pressure rod assembly to move down and load the sample to be tested until the sample to be tested falls off the inner wall of the outer mold, and the corresponding failure load is recorded. F yi .
[0012] Based on further optimization of the above solution, the loading speed of the universal testing machine is 0.5-4 mm / min.
[0013] Based on the further optimization of the above scheme, the specific method of constructing the continuous section model in step E is: First, import the cross-sectional morphology image obtained by the 3D scanner and segment it using the optimal threshold segmentation: Calculate each gray level i Probability of occurrence p i :
[0014] Where: n i Indicates the gray level in the image isi The number of N Represents the total number of pixels in the image; For a given threshold t , respectively obtain the gray level range 0~t With grayscale range t+1~L-1 (L is the total number of gray levels) w 1 and w 2:
[0015] Get the between-class variance of the two gray levels :
[0016] Traverse all thresholds in the grayscale range 0 to L-1 t , so that the between-class variance Maximum value t max , that is, the optimal threshold; Gray level is greater than the optimal threshold t max The pixel point is the broken pixel point; Then, all the broken pixels are counted and recorded as (x 1 ,y 1 ),( x 2 ,y 2 ),…,( x n+1 ,y n+1 ) , obtain the continuous fracture surface through the fracture pixel points:
[0017] Where: x i 、x j Indicates the value of the independent variable; y i Indicates the independent variable x i The corresponding function value, and x i Different from each other.
[0018] Based on the further optimization of the above scheme, the specific method for obtaining the fracture area of the sample to be tested in step E is: The obtained continuous fracture surface is arbitrarily decomposed into N A small area, denoted as , then the area of the continuous fracture surface A i for:
[0019] Where: a i ,b i ) represents each small area (i=1,2,…,N) Any point within; Represents each small area (i=1,2,…,N) The maximum value of the diameter.
[0020] The following are the technical effects of the solution of the present invention: Compared with the traditional shear strength test method of flat sample, the scheme of the present invention effectively avoids mutual interference between the inner and outer surfaces during the shear strength test by loading and testing the inner and outer surfaces of the annular coating component separately, reduces test errors, and ensures the accuracy and validity of the test data; at the same time, the method of the present invention effectively solves the problems of difficulty in bonding and curing annular samples, mutual influence of inner and outer surfaces, and difficulty in accurately calibrating fracture surfaces, and can quickly, accurately and effectively complete the shear strength test of thick annular coating samples, thereby providing reliable and effective data support for performance evaluation and material research and development of annular coating samples. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Schematic diagram of the bonding and curing of the adhesive film of the test sample in the embodiment of the present invention.
[0022] Figure 2 It is a schematic diagram of loading test of the sample to be tested in an embodiment of the present invention.
[0023] Figure 3 It is a cross-sectional view of a loading test of the inner wall coating of a test sample in an embodiment of the present invention.
[0024] Figure 4 It is a cross-sectional view of a loading test of the outer wall coating of a test sample in an embodiment of the present invention.
[0025] Figure 5 for Figure 4 AA section view.
[0026] Among them, 10, the sample to be tested; 20, the film; 31, the outer mold; 32, the inner mold; 41, the lower tooling; 42, the upper tooling; 51, the support plate; 52, the support seat; 53, the positioning nesting; 54, the pressure plate; 551, the connecting seat; 552, the pressure rod; 56, the limit sleeve. DETAILED DESCRIPTION
[0027] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0028] Embodiment 1: A method for testing the shear strength of an annular coating component, comprising: Step A, mold design: Split the annular coating sample in half (i.e., obtain a semi-annular test sample 10), and design a curing mold and a curing tooling according to the split test sample 10 (the appearance and size of the curing mold correspond to the test sample 10); refer to Figure 1 As shown: the curing mold includes an outer mold 31 and an inner mold 32, and the outer mold 31 is composed of a coaxial cylindrical portion and a semi-annular portion (the semi-annular portion and one end of the cylindrical portion are integrally formed, as shown in FIG. Figure 1 As shown, the semi-circular portion is arranged corresponding to the sample to be tested 10, and the inner wall of the semi-circular portion can fit with the outer wall of the sample to be tested 10, and the two side planes of the semi-circular portion are flush with the two sections of the sample to be tested 10 (as shown in FIG. Figure 1 As shown in FIG. 1 ), the inner diameter and outer diameter of the cylindrical portion are consistent with the semi-circular portion; the inner mold 32 is set to a rod-shaped structure corresponding to the inner circle of the test sample 10 (that is, the outer wall of the inner mold 32 can fit the inner wall of the test sample 10, as shown in FIG. Figure 1 The curing tooling includes an upper tooling 42 and a lower tooling 41. The lower tooling 41 is provided with a first slot (as shown) corresponding to the outer wall of the outer mold 31. Figure 1 Su Sohu), the upper tooling 42 is provided with a second slot (such as Figure 1 as shown).
[0029] Step B, coating the adhesive film 20: uniformly coating the adhesive film 20 on the inner and outer surfaces of the sample 10 to be tested, wherein the adhesive film 20 is any one of E-7 two-component epoxy adhesive or Fm-1000 solid adhesive film; and fixing the sample 10 to be tested coated with the adhesive film 20 by a curing mold and a curing tool, specifically: first, clamping the outer mold 31 in the first card slot; then, placing the sample 10 to be tested coated with the adhesive film 20 on the inner and outer surfaces of the semi-circular portion, ensuring that the inner wall of the semi-circular portion and the outer wall of the sample 10 to be tested are in contact with each other; The walls are in contact with each other and the cross-section of the test sample 10 is flush with the plane of the semi-circular portion; then, the inner mold 32 is passed through the inner circle of the test sample 10 and the outer wall of the inner mold 32 is closely fitted with the inner circle of the test sample 10; finally, the upper tooling 42 is clamped on the outer wall of the inner mold 32, so that the outer wall of the second clamping groove is respectively fitted with the plane of the semi-circular portion, the cross-section of the test sample 10, and the outer wall of the inner mold 32, and the upper tooling 42 and the lower tooling 41 are fixed by limiting bolts to ensure close contact between the coating, the film 20 and the inner and outer molds 31.
[0030] Step C, bonding and curing: put the curing tooling in step B into an electric hot air drying oven for heating and curing, the curing temperature is 150-250°C (preferably 200°C), and the heat preservation time is 120-180min (preferably 150min); after curing, the test sample 10 is cooled to room temperature (generally 20-25°C), the curing mold is taken out and the residual adhesive around the test sample 10 is removed; Step D, loading test: Place the test sample 10 and the curing mold on the universal testing machine through a clamping tool so that the test sample 10 is subjected to a vertical force (such as Figure 2 As shown); the clamping tool includes a support plate 51, a support seat 52, a positioning nest 53, a pressure plate 54 and a pressure rod assembly (combined Figure 3 and Figure 5 As shown in the figure, a support seat 52 is fixedly arranged on the end face of the support plate 51, and a positioning nest 53 is detachably arranged on the end face of the support seat 52. The outer wall of the support seat 52 corresponds to the inner wall of the outer mold 31, and a through hole is arranged in the middle of the positioning nest 53 corresponding to the inner mold 32; a pressure rod assembly is detachably arranged on the bottom face of the pressure plate 54, including a connecting seat 551 and a plurality of pressure rods 552, the connecting seat 551 is detachably connected to the bottom plate of the pressure plate 54, and a plurality of pressure rods 552 are evenly arranged on the bottom face of the connecting seat 551 and corresponding to the sample to be tested 10 (the number of the pressure rods 552 is determined according to the diameter of the pressure rod 552, the circumference of the sample to be tested 10, and the uniformity of the action of the pressure rod 552 on the sample to be tested 10, and it is necessary to avoid the pressure rod 552 from damaging the top face of the sample to be tested 10; as shown in the figure, a support seat 52 is fixedly arranged on the end face of the support plate 51, and a positioning nest 53 is detachably arranged on the end face of the support plate 51, and a positioning nest 53 is detachably arranged on the end face of the support plate 51, and a plurality of pressure rods 552 are evenly arranged on the bottom face of the connection seat 551 and corresponding to the sample to be tested 10 (the number of the pressure rods 552 is determined according to the diameter of the pressure rod 552, the circumference of the sample to be tested 10, and the uniformity of the action of the pressure rod 552 on the sample to be tested 10, and it is necessary to avoid the pressure rod 552 from damaging the top face of the sample to be tested 10; as shown in the Figure 5 As shown, in this embodiment, the pressure rods 552 are set to 5).
[0031] Start the universal testing machine and perform a loading test on the test sample 10. The specific method is as follows: First, the support plate 51 is placed on the end surface of the support table of the universal testing machine and a positioning nest 53 (such as Figure 3 As shown in FIG. 1 ), the curing mold with the sample to be tested 10 in step C is placed on the end surface of the support plate 51, wherein the bottom inner wall of the outer mold 31 contacts the outer wall of the support seat 52 (to achieve the positioning of the curing mold and the sample to be tested 10) and the top of the positioning nest 53 contacts the bottom surface of the sample to be tested 10, thereby positioning the curing mold and completing the support of the sample to be tested 10; at the same time, the pressing plate 54 without the pressing rod assembly is installed on the loading end of the universal testing machine; Then, the universal testing machine is started, the pressing plate 54 is moved downward, and the inner mold 32 is loaded (in this process, the positioning nesting 53 limits the inner mold 32 that moves downward to prevent the inner mold 32 from being offset due to the loading force, which affects the accuracy of the inner wall shear strength test). The loading speed of the universal testing machine is 0.5-4 mm / min (preferably 2.5 mm / min) until the inner mold 32 falls off the inner wall of the test sample 10, and the corresponding failure load is recorded. F xi; Finally, the universal testing machine is reset, the outer mold 31 with the test sample 10 is removed, the positioning nest 53 on the support seat 52 is removed, and the pressure rod assembly is installed on the bottom surface of the pressure plate 54 (such as Figure 4 As shown in the figure, the outer mold 31 with the test sample 10 is placed on the support plate 51 again (the support seat 52 is used to limit the position so that the outer mold 31 and the pressure rod assembly are coaxial), and the universal testing machine is started, so that the pressure plate 54 drives the pressure rod assembly to move downward and load the test sample 10 (that is, the bottom end of the pressure rod 552 gradually contacts the top surface of the test sample 10 and supports the test sample 10 to move downward). The loading speed of the universal testing machine is 0.5-4mm / min (preferably 2.5mm / min) until the test sample 10 falls off the inner wall of the outer mold 31, and the corresponding failure load is recorded. F yi .
[0032] Step E, calibrating the fracture surface: after the loading test is completed, take out the test sample 10, and use a three-dimensional scanner to scan the surface of the test sample 10; Construct a continuous section model, specifically: First, import the cross-sectional morphology image obtained by the 3D scanner and segment it using the optimal threshold segmentation: Calculate each gray level i Probability of occurrence p i :
[0033] Where: n i Indicates the gray level in the image is i The number of N Represents the total number of pixels in the image; For a given threshold t , respectively obtain the gray level range 0~t With grayscale range t+1~L-1 (L is the total number of gray levels) w 1 and w 2:
[0034] Get the between-class variance of the two gray levels :
[0035] Traverse all thresholds in the grayscale range 0 to L-1 t , so that the between-class variance Maximum value t max , that is, the optimal threshold; Gray level is greater than the optimal threshold t max The pixel point is the broken pixel point; Then, all the broken pixels are counted and recorded as (x 1 ,y 1 ),( x 2 ,y 2 ),…,( x n+1 ,y n+1 ) , obtain the continuous fracture surface through the fracture pixel points:
[0036] Where: x i 、x j Indicates the value of the independent variable; y i Indicates the independent variable x i The corresponding function value and x i Different from each other.
[0037] And obtain the fracture area of the test sample 10, specifically: The obtained continuous fracture surface is arbitrarily decomposed into N A small area, denoted as , then the area of the continuous fracture surface A i for:
[0038] Where: a i ,b i ) represents each small area (i=1,2,…,N) Any point within; Represents each small area (i=1,2,…,N) The maximum value among the diameters; The fracture surface area of the inner wall of the test sample 10 is obtained by the above method. A xi and the fracture surface area of the outer wall A yi .
[0039] Step F, data processing: The shear strength is obtained by the failure load and fracture area of the loading test, namely:
[0040]
[0041] Where: , They respectively represent the ratio of the inner wall coating area of the annular coating component to the total inner and outer wall areas of the annular coating and the ratio of the outer wall coating area of the annular coating component to the total inner and outer wall areas of the annular coating; Indicates the shear strength of a single annular coating member; A plurality of annular coating components of the same size and material can be tested simultaneously, and the final shear strength of the annular coating component can be obtained by taking the average shear strength value between them.
[0042] Embodiment 2: As another preferred embodiment of the present invention, in order to limit the shear strength of the outer wall of the test sample 10 when testing the shear strength, and avoid damage to the end face of the test sample 10 or inaccurate testing caused by the displacement of the pressure rod 552, on the basis of the scheme of embodiment 1, a limiting sleeve 56 (such as Figure 3 , Figure 4 As shown, the inner wall of the limit sleeve 56 corresponds to the outer wall of the outer mold 31 and the height of the limit sleeve 56 is greater than the overall height of the pressure rod assembly, ensuring that when the bottom end of the pressure rod 552 contacts the end surface of the test sample 10, the inner wall of the bottom of the limit sleeve 56 slides in contact with the outer wall of the cylindrical portion of the outer mold 31 (as shown in FIG. Figure 4 As shown in the figure), a hard limit is formed on the pressing process.
[0043] Embodiment 3: As another preferred embodiment of the present invention, based on the solution of Embodiment 1 or Embodiment 2, a buffer layer (a rubber buffer layer may be used) is provided on the end surfaces of the support plate 51 and the support seat 52 to avoid damage caused by excessive loading and extrusion.
Claims
1. A method for testing the shear strength of an annular coating component, characterized in that: include: Step A, mold design: cut the annular coating sample in half, and design a curing mold and a curing tooling according to the cut sample to be tested; Step B, coating the adhesive film: uniformly coating the adhesive film on the inner and outer surfaces of the sample to be tested, and fixing the sample to be tested coated with the adhesive film by a curing mold and a curing tool; Step C, bonding and curing: placing the curing tooling in step B into an electric hot air drying oven for heating and curing; after curing, the sample to be tested is cooled to room temperature, the curing mold is taken out, and the residual adhesive around the sample to be tested is removed; Step D, compression test: Place the sample to be tested and the curing mold on a universal testing machine through a clamping tool so that the sample to be tested is subjected to a vertical force; Start the universal testing machine and perform a loading test on the test sample; Step E, calibrating the fracture surface: after the loading test is completed, the sample to be tested is taken out, and the surface of the sample to be tested is scanned by a three-dimensional scanner to construct a continuous cross-section model, and the fracture area of the sample to be tested is obtained; Step F, data processing: obtaining the shear strength through the failure load and fracture area of the loading test.
2. A method for testing the shear strength of an annular coating component according to claim 1, characterized in that: In step A, the curing mold includes an outer mold and an inner mold. The outer mold consists of a coaxial cylindrical portion and a semi-annular portion. The semi-annular portion is arranged corresponding to the sample to be tested, and the inner wall of the semi-annular portion can fit the outer wall of the sample to be tested, the two side planes of the semi-annular portion are flush with the two sections of the sample to be tested, and the inner diameter and outer diameter of the cylindrical portion are consistent with those of the semi-annular portion; the inner mold is arranged as a rod-shaped structure corresponding to the inner circle of the sample to be tested.
3. A method for testing the shear strength of an annular coating component according to claim 1 or 2, characterized in that: In step B, the adhesive film is any one of E-7 two-component epoxy adhesive or Fm-1000 solid adhesive film.
4. A method for testing the shear strength of an annular coating component according to claim 3, characterized in that: In step B, the curing tooling includes an upper tooling and a lower tooling, wherein the lower tooling is provided with a first slot corresponding to the outer wall of the outer mold, and the upper tooling is provided with a second slot corresponding to the semi-circular portion plane, the cross section of the sample to be tested and the outer wall of the inner mold; the specific installation method is: first, the outer mold is clamped in the first slot; then, the sample to be tested with the inner and outer surfaces coated with adhesive film is placed on the inner wall of the semi-circular portion, ensuring that the inner wall of the semi-circular portion fits with the outer wall of the sample to be tested and the cross section of the sample to be tested is flush with the plane of the semi-circular portion; then, the inner mold is passed through the inner circle of the sample to be tested and the outer wall of the inner mold is tightly fitted with the inner circle of the sample to be tested; finally, the upper tooling is clamped on the outer wall of the inner mold, so that the outer wall of the second slot is respectively fitted with the semi-circular portion plane, the cross section of the sample to be tested and the outer wall of the inner mold, and the upper tooling and the lower tooling are fixed by limit bolts.
5. A method for testing the shear strength of an annular coating component according to claim 3, characterized in that: The clamping tool includes a support plate, a support seat, a positioning nest, a pressure plate and a pressure rod assembly. The support seat is fixedly arranged on the end face of the support plate and the positioning nest is detachably arranged on the end face of the support seat. The outer wall of the support seat corresponds to the inner wall of the outer mold and a through hole is arranged in the middle of the positioning nest corresponding to the inner mold; the pressure rod assembly is detachably arranged on the bottom surface of the pressure plate, including a connecting seat and multiple pressure rods. The connecting seat is detachably connected to the bottom plate of the pressure plate, and multiple pressure rods are evenly arranged on the bottom surface of the connecting seat and corresponding to the sample to be tested.
6. A method for testing the shear strength of an annular coating component according to claim 5, characterized in that: The specific method of performing the loading test on the sample to be tested in step D is: First, the support plate is placed on the end surface of the support table of the universal testing machine and a positioning nest is set on the support seat, and the curing mold with the sample to be tested in step C is placed on the end surface of the support plate, wherein the bottom inner wall of the outer mold contacts the outer wall of the support seat and the top of the positioning nest contacts the bottom surface of the sample to be tested, thereby positioning the curing mold and completing the support of the sample to be tested; at the same time, the pressure plate without the pressure rod assembly is installed on the loading end of the universal testing machine; Then, start the universal testing machine, move the pressure plate downward, load the inner mold until the inner mold falls off the inner wall of the test sample, and record the corresponding failure load. F xi ; Finally, the universal testing machine is reset, the outer mold with the sample to be tested is removed, the positioning nest on the support seat is removed, and the pressure rod assembly is installed on the bottom of the pressure plate. The outer mold with the sample to be tested is placed on the support plate again, and the universal testing machine is started, so that the pressure plate drives the pressure rod assembly to move down and load the sample to be tested until the sample to be tested falls off the inner wall of the outer mold, and the corresponding failure load is recorded. F yi .
7. A method for testing the shear strength of an annular coating component according to claim 1, characterized in that: The specific method of constructing the continuous section model in step E is: First, import the cross-sectional morphology image obtained by the 3D scanner and segment it using the optimal threshold segmentation: Calculate each gray level i Probability of occurrence p i : Where: n i Indicates the gray level in the image is i The number of N Represents the total number of pixels in the image; For a given threshold t , respectively obtain the gray level range 0~t With grayscale range t+1~L-1 Probability w 1 and w 2: Get the between-class variance of the two gray levels : Traverse the grayscale range 0~L-1 All thresholds in t , so that the between-class variance Maximum value t max , that is, the optimal threshold; Gray level is greater than the optimal threshold t max The pixel point is the broken pixel point; Then, all the broken pixels are counted and recorded as (x 1 ,y 1 ),( x 2 ,y 2 ),…,( x n+1 ,y n+1 ) , obtain the continuous fracture surface through the fracture pixel points: Where: x i 、x j Indicates the value of the independent variable; y i Indicates the independent variable x i The corresponding function value, and x i Different from each other.
8. A method for testing the shear strength of an annular coating component according to claim 7, characterized in that: The specific method for obtaining the fracture area of the sample to be tested in step E is: The obtained continuous fracture surface is arbitrarily decomposed into N A small area, denoted as , then the area of the continuous fracture surface A i for: Where: a i ,b i ) represents each small area Any point within; Represents each small area The maximum value among the diameters.